Uncovering the crystal defects within aragonite CaCO - San, Xingyuan; Gong, Mingyu; Wang, Jian; Ma, Xiuliang; dos Reis, Roberto; Smeets, Paul J. M.; Dravid, Vinayak P.; Hu, Xiaobing (Proceedings of the National Academy of Sciences - PNAS, 2022)
Knowledge of deformation mechanisms in aragonite, one of the three crystalline polymorphs of CaCO₃, is essential to understand the overall excellent mechanical performance of nacres. Dislocation slip and deformation twinning were claimed previously as plasticity carriers in aragonite, but crystallographic features of dislocations and twins have been poorly understood. Here, utilizing various transmission electron microscopy techniques, we reveal the atomic structures of twins, partial dislocations, and associated stacking faults. Combining a topological model and density functional theory calculations, we identify complete twin elements, characters of twinning disconnection, and the corresponding twin shear angle (∼8.8°) and rationalize unique partial dislocations as well. Additionally, we reveal an unreported potential energy dissipation mode within aragonite, namely, the formation of nanograins via the pile-up of partial dislocations. Based on the microstructural comparisons of biogenic and abiotic aragonite, we find that the crystallographic features of twins are the same. However, the twin density is much lower in abiotic aragonite due to the vastly different crystallization conditions, which in turn are likely due to the absence of organics, high temperature and pressure differences, the variation in inorganic impurities, or a combination thereof. Our findings enrich the knowledge of intrinsic crystal defects that accommodate plastic deformation in aragonite and provide insights into designing bioengineering materials with better strength and toughness.